Praktik Manajemen Sumber Daya Manusia dan Kinerja Badan Usaha Milik Desa: Studi Kualitatif dari Kabupaten Lebak, Indonesia - Akhmad Priharjanto; Yuniarto Hadiwibowo; Rokhmat Taufiq Hidayat (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to provide an in-depth understanding of how Human Resource Management (HRM) practices are enacted within Village-Owned Enterprises (VOE) and how these practices shape organizational performance in a rural context. Specifically, this study seeks to explore the ways in which recruitment practices, competency development, leadership, motivation, and managerial commitment are implemented in the management of VOE and how these practices are experienced by key organizational actors. Research Methodology: This study employs a qualitative case study approach conducted in selected villages in Lebak Regency, Indonesia. Data were collected through in-depth interviews with VOE managers, village government officials, village supervisory bodies, and district-level officials from the Village Community Empowerment Office, complemented by observations and document analysis. Results: The findings reveal that VOE performance is constrained by interrelated HRM problems, including non?competency-based recruitment practices, limited training and capacity-building support particularly in core business development and financial management and weak supervisory roles of village institutions. These conditions result in limited managerial competence, weak organizational learning, and reduced accountability. Conclusions: The study concludes that VOE performance is fundamentally shaped by human resource capacity and governance processes rather than purely financial or structural factors. Limitations: This study is limited to selected cases in one district and relies on qualitative data, which may limit generalizability. Contributions: This study contributes to applied management literature by providing contextual qualitative insights into HRM practices in village-owned enterprises and offering practical implications for policy institutions and village managers.